2022
DOI: 10.1111/bju.15739
|View full text |Cite
|
Sign up to set email alerts
|

Functional and quality of life outcomes of localised prostate cancer treatments (Prostate Testing for Cancer and Treatment [ProtecT] study)

Abstract: ConclusionTreatment decision-making for localised prostate cancer can be informed by these 6-year functional and QoL outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…shown that active monitoring of PCa would achieve a similar overall survival as radical treatment, while enduring less treatment related side-effects (2). However, in this same cohort, Active Surveillance (AS) had a higher risk of disease progression and of metastatic disease (3).…”
Section: Original Papermentioning
confidence: 78%
“…shown that active monitoring of PCa would achieve a similar overall survival as radical treatment, while enduring less treatment related side-effects (2). However, in this same cohort, Active Surveillance (AS) had a higher risk of disease progression and of metastatic disease (3).…”
Section: Original Papermentioning
confidence: 78%
“…AS should be considered as the treatment of choice for the majority of PCa patients with localized disease, as it does not compromise survival while significantly improving quality of life [ 1 , 3 ]. However, interventional methods of treatment are not exclusive but complementary, as approximately half of the patients will eventually receive active treatment [ 1 , 25 ], and some will decline AS to start off with.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 50% of diagnosed patients do not require immediate interventional treatment. Randomized clinical trials have shown that active surveillance (AS) does not compromise survival [ 1 ], while it significantly improves quality of life (QoL) and functional outcomes [ 2 , 3 ] in patients with localized disease. Current clinical guidelines recommend AS as the preferred method of treatment for patients with low-risk (LR) cancer, and as a viable option for favourable intermediate-risk group (IR) PCa [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unnecessary treatment of PCa patients whose life expectancy is insufficient for the treatment to have a noticeable impact on their survival can be associated with the risk of side effects and can significantly reduce the patient’s quality of life [ 23 , 24 ]. A personalized approach to the treatment of each patient requires a proper estimation of their life expectancy, especially if aggressive treatment is planned.…”
Section: Discussionmentioning
confidence: 99%